(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
Objective: To determine perinatal mortality and its related risk factors in Dhaka National Medical College Hospital. Study design: Prospective observational study. Setting: Obstetrics and Gynaecology Department in Dhaka National Medical College Hospital from January to December 2011. Patients and Methods: All perinatal deaths including stillbirths (SBs) and early neonatal deaths (ENNDs) within 0-7 days of delivery after 28 wks of gestation were studied during the study period, while pregnancies <28 wks of gestation were excluded from the study. The relevant information was collected through a pre-designed data sheet. Results: A total number of 1882 deliveries were analysed for perinatal mortality (PNM). Among them, there were 41 perinatal deaths (PNDs) giving a perinatal mortality of 21.78/1000 births. There were 36 SBs and 05 ENNDs. Out of all patients, 58.53% women were multipara and 75.61% were booked case. Common risk factors for PNM were hypertensive disorders in pregnancy (26.82%), followed by antepartum haemorrhage (9.75%) and congenital anomalies (9.75%). Malpresentation were found in 7.31% of PNDs, while prolonged labour and prematurity both contribute to 4.87% . In 2.43% cases, septicaemia of neonate and maternal medical disorder (Gestational diabetes mallitus) was the underlying cause. However, in 31.7% cases cause was unknown. Conclusion: The perinatal mortality in present study is not so high. Many of the causes of perinatal death though unknown but other risk factors can be prevented. J. Dhaka National Med. Coll. Hos. 2014;20(01):41-46